Seasonal Variability of Some Enteromorpha Species in Kanyakumari Region, the Southern Coast of Tamil Nadu - J, John Peter Paul; D., Patric Raja (Asian Journal of Biological and Life Sciences, 2012)
The present report deals with the study of seasonal variation of some Enteromorpha species in Kanyakumari region, the southern coast of Tamil Nadu. Kanyakumari region was divided in to four stations namely Kanyakumari, Chinna Muttam, Arockiapuram and Vattakottai. Monthly survey was 2 carried out regularly from January 2007 to December 2010. The seaweed species were enumerated at random using a quadrate (0.5m ). Atotal of three species of Enteromorpha were collected in the study area such as Enteromorpha compressa, Enteromorpha flexuosa and Enteromorpha linza. The frequency and density were calculated and all the Enteromorpha species showed a similar pattern of seasonal variation. Among the species collected the highest frequency (53.75%) and density (5.53) were observed in Enteromorpha linza during summer season and the lowest frequency (37.50%) in Enteromorpha compressa and density (1.26) in Enteromorpha flexuosa were recorded during post-monsoon season. From the present investigation, it was concluded that all the Enteromorpha species (Chlorophyceae) exhibited the maximum frequency and density during the summer season followed by the declined trend was observed in the successive seasons. During the post-monsoon season the frequency and density of Enteromorpha species (Chlorophyceae) was minimum in the selected region of southern coast of Tamil Nadu.